Analysis of 3-Dimensional Arch Anatomy, Vascular Flow, and Postnatal Outcome in Cases of Suspected Coarctation of the Aorta Using Fetal Cardiac Magnetic Resonance Imaging. (July 2021) - Lloyd, David F.A.; van Poppel, Milou P.M.; Pushparajah, Kuberan; Vigneswaran, Trisha V.; Zidere, Vita; Steinweg, Johannes; van Amerom, Joshua F.P.; Roberts, Thomas A.; Schulz, Alexander; Charakida, Marietta; Miller, Owen; Sharland, Gurleen; et al.
Abstract : Background: Identifying fetuses at risk of severe neonatal coarctation of the aorta (CoA) can be lifesaving but is notoriously challenging in clinical practice with a high rate of false positives. Novel fetal 3-dimensional and phase-contrast magnetic resonance imaging (MRI) offers an unprecedented means of assessing the human fetal cardiovascular system before birth. We performed detailed MRI assessment of fetal vascular morphology and flows in a cohort of fetuses with suspected CoA, correlated with the need for postnatal intervention. Methods: Women carrying a fetus with suspected CoA on echocardiography were referred for MRI assessment between 26 and 36 weeks of gestation, including high-resolution motion-corrected 3-dimensional volumes of the fetal heart and phase-contrast flow sequences gated with metric optimized gating. The relationship between aortic geometry and vascular flows was then analyzed and compared with postnatal outcome. Results: Seventy-two patients (51 with suspected fetal CoA and 21 healthy controls) underwent fetal MRI with motion-corrected 3-dimensional vascular reconstructions. Vascular flow measurements from phase-contrast sequences were available in 53 patients. In the CoA group, 25 of 51 (49%) required surgical repair of coarctation after birth; the remaining 26 of 51 (51%) were discharged without neonatal intervention. Reduced blood flow in the fetal ascending aorta and at the aortic isthmus was associated with increasing angulation ( P =0.005) and proximal displacement ( P =0.006) of the isthmus and was seen in both true positive and false positive cases. A multivariate logistic regression model including aortic flow and isthmal displacement explained 78% of the variation in outcome and correctly predicted the need for intervention in 93% of cases. Conclusions: Reduced blood flow though the left heart is associated with important configurational changes at the aortic isthmus in fetal life, predisposing to CoA when the arterial duct closes after birth. Novel fetal MRI techniques may have a role in both understanding and accurately predicting severe neonatal CoA. Abstract : Supplemental Digital Content is available in the text.